(untitled) (Studia Prawnicze / The Legal Studies, 2023)
Responsibility for the decisions and for the activity in the domain of nation- al economy presently constitutes one of the most important issues in the theory and practice of the functioning of the economy in the socialist countries. The Author begins with the assumption that the scope and the system of responsibility must be closely connected with the scope of competences of the economic units. Thus discussing the issue of the system of responsibility in contractual relationships the Author connects it closely with the scope, of freedom of contracts of the parties in socialized trade. Applying the civil law to the contractual relationships in the socialized trade means that the principle of the freedom of contracts is thoroughly binding. There is however another concurring principle of organizational and structural character — this is the principle of central planning and managing of the economy. The latter principle means that the organs of the management are allowed to intervene into the sphere of the activity of an enterprise, also in their contractual relations. In order to make the system of management flexible the scope of such interventions was never defined but in practice we can observe a constant tendency to widen it to the detriment od contractual freedom of the enterprises. In extreme cases the contracts thus concluded between the enterprises become just an outer form of the decisions made by the organs of the management and they do not represent the proper decisions of the economic enterprises. Na- turally, the parties to the contracts actually imposed to them are not interested in their realization. This is the reason why it was necessary to include into the system of contractual responsibility a specific sanction in the form of so called “contractual penalties” obligatory also as far as their vindication is concerned. Tn practice however the system of responsibility based on this type of sanctions is not efficacious. After having discussed various reasons of the present state of affairs the Author comes to the conclusion that the solution to the problem of efficacity of the system of responsibility in socialized trade does not lie in development of prerequisits of the responsibility or in the sanctions foreseen. Efficacity of the civil law instruments requires such shape of organizational structure and of the competences in national economy that would enable the decisions concerning the economic activity and the responsibility for this activity to be localized in one center. This suggestion leads in particular to the limitation of the interventions from the outside into the contractual relations of the units of socialized economy.